Mechanism of a charge-coupled device (CCD) sensor on particles' characterisation using tomographic techniques - Idroas, Mariani; Ibrahim, Muhammad Nasir; Othman, Norasikin (Faculty of Chemical and Natural Resource Engineering, 2008)
The mechanism of a charge-coupled device (CCD) linear image sensor using a four-projection optical tomography is studied. The CCD linear image sensor used in the study is a Sony ILX551A which has 2048 pixels, with a pixel size of 14- microns. The interaction of light with a solid particle is based on the Beer-Lambert Law of Light Absorption. The shadow of the particle will be casted on several pixels of the linear image sensor, and the behavior of the affected pixels is investigated. The exact location of edges of the object is crucial in order to achieve accurate particle size measurements. The simplest method used in determining the position of edges of the particle is by comparing the sensor output signal with a threshold level. The threshold level is set to 25% of the signal’s amplitude; this follows from the analysis of the light diffraction on the edge of the measured object illuminated by a parallel light source.